Potentials of a friction-induced recycling process to improve resource and energy efficiency in manufacturing technology - Borgert, Thomas; Milaege, Dennis; Schweizer, Swetlana; Homberg, Werner; Schaper, Mirko; Tröster, Thomas (International Journal of Material Forming)
Abstract Efforts to enhance sustainability in all areas of life are increasing worldwide. In the field of manufacturing technology, a wide variety of approaches are being used to improve both resource and energy efficiency. Efficiency as well as sustainability can be improved by creating a circular economy or through energy-efficient recycling processes. As part of the interdisciplinary research group "Light—Efficient—Mobile" investigations on the energy-efficient friction-induced recycling process have been carried out at the department of Forming and Machining Technology at Paderborn University. E.g. using the friction-induced recycling process, different formless solid aluminum materials can be direct recycled into semi-finished products in an energy-efficient manner. The results of investigations with regard to the influence of the geometrical shape and filling rate of the aluminum particles to be recycled as well as the rotational speed of the continuously rotating wheel are explained in this paper. In addition to the recycling of aluminum chips, aluminum particles like powders from the field of additive manufacturing are processed. Based on these results, the future potentials of solid-state recycling processes and their contribution to the circular economy are discussed. The main focus here is on future interdisciplinary research projects to achieve circularity in the manufacturing of user-individual semi-finished products as well as the possibility to selectively adjust the product properties with the continuous recycling process.
Keywords: General Materials Science

Thermodynamic multifield modeling of electromagnetic metal forming - Unger, J.; Ostwald, Richard; Svendsen, B. (International Journal of Material Forming)